2020
DOI: 10.1504/ijbpm.2020.106104
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Islamic banking and bank customer satisfaction in Afghanistan: an exploratory analysis

Abstract: Islamic banking and finance is one of the fastest growing sectors of the Afghan economy. Through the lens of the theory of reasoned action (TRA), we focus on customers' knowledge of Islamic banking and attitudes of Islamic bank customers towards Islamic banking products as well as the factors that determine Afghans' selection of Islamic banking versus conventional banking products in Kabul. We examine the products used by bank customers and their motivations for using Islamic products as an alternative to avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
5
0
3
Order By: Relevance
“…Akan tetapi fakta bahwa marketshare bank syariah menduduki posisi minoritas (6%) dari aset bank konvensional merupakan suatu hal yang disayangkan dan perlu dikaji lebih lanjut penyebabnya. Tentu banyak faktor yang menyebabkan kondisi ini terjadi, beberapa antisipasi yang memungkinkan terjadinya ironi itu adalah mungkin banyak masyarakat kurang mengenal baik bank syariah (Mulia et al 2020), pengetahuan masyarakat masih rendah mengenai bank syariah (Saptasari & Aji, 2020;Safi et al 2020) dan pemahaman ummat pada bank syariah masih rendah (Ratnasari, 2020).…”
Section: A Pendahuluanunclassified
See 2 more Smart Citations
“…Akan tetapi fakta bahwa marketshare bank syariah menduduki posisi minoritas (6%) dari aset bank konvensional merupakan suatu hal yang disayangkan dan perlu dikaji lebih lanjut penyebabnya. Tentu banyak faktor yang menyebabkan kondisi ini terjadi, beberapa antisipasi yang memungkinkan terjadinya ironi itu adalah mungkin banyak masyarakat kurang mengenal baik bank syariah (Mulia et al 2020), pengetahuan masyarakat masih rendah mengenai bank syariah (Saptasari & Aji, 2020;Safi et al 2020) dan pemahaman ummat pada bank syariah masih rendah (Ratnasari, 2020).…”
Section: A Pendahuluanunclassified
“…3, No. 1, Oktober 2022, 16-32 ISSN: 2747-0474; E-ISSN: 2747-0482 (Mulia et al 2020), faktor pengetahuan ummat terhadap bank syariah belum kuat (Saptasari & Aji, 2020;Safi et al 2020), faktor religiusitas ummat belum konsisten (Abror et al 2019), faktor pemerintah mengutamakan bank konvensional dan belum memberi kepercayaan pada bank syariah (Sari et al 2019), dan sebagainya.…”
Section: A Pendahuluanunclassified
See 1 more Smart Citation
“…Prior studies that discussed customer satisfaction in Islamic business discussed customer satisfaction of Islamic bank customers. These studies have been carried out by Ahmed et al (2022), De Bruin et al (2021), Fida et al (2020, Zouari & Abdelhedi (2021), Aini (2018), Jawaid et al (2021), Rama (2020), Mariyanti et al (2021), Haron et al (2020, Jan & Shafiq (2021), Purnama et al (2021), Safi et al (2020), Syaifuddin et al (2022), Anouze et al (2019), andRiduwan et al (2022). Research on consumer satisfaction in Islamic banks is analyzed using the SERVQUAL framework (Ali & Raza, 2017;De Bruin et al, 2021;Janahi & Al Mubarak, 2017;Zouari & Abdelhedi, 2021).…”
Section: Exploration Determinants Of Customer Satisfactionmentioning
confidence: 99%
“…According to (Zuhirsyan & Nurlinda, 2018), partially religiosity is more influential on the decision to choose a sharia bank than perception. In the case in Afghanistan (Safi et al, 2020) found that customer choice of Islamic bank products is influenced by the variable of religiosity (religious belief). The same thing was also found in Indonesia by (Reni & Ahmad, 2016), which stated that in addition to variables such as subject norms, knowledge, and government support, religion also has a significant influence on people's intention to choose Islamic banks.…”
Section: Literature Reviewmentioning
confidence: 99%